2021
DOI: 10.1186/s13104-021-05705-6
|View full text |Cite
|
Sign up to set email alerts
|

Pleth variability index and fluid management practices: a multicenter service evaluation

Abstract: Objectives The introduction of a new technology has the potential to modify clinical practices, especially if easy to use, reliable and non-invasive. This observational before/after multicenter service evaluation compares fluid management practices during surgery (with fluids volumes as primary outcome), and clinical outcomes (secondary outcomes) before and after the introduction of the Pleth Variability Index (PVI), a non-invasive fluid responsiveness monitoring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the PVI group, the initial lactate value was 14 We compared the lactate levels at 6 h after the surgery which is at a different timing than the previous study and could not find a significant difference. Increasing the number of ABG would add to the cost of the study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the PVI group, the initial lactate value was 14 We compared the lactate levels at 6 h after the surgery which is at a different timing than the previous study and could not find a significant difference. Increasing the number of ABG would add to the cost of the study.…”
Section: Discussionmentioning
confidence: 94%
“…Our results agree to the conclusion of Forget et al, who reported a significant decrease in crystalloid (P=0.004) and total fluid (P=0.049). 14 Thus, the use of the non-invasive PVI appears to be better than the traditional hemodynamic parameters such as CVP in predicting fluid responsiveness. These data support previous work showing that plethysmography variability can predict fluid responsiveness in cardiac, general surgical, and intensive care patients.…”
Section: Discussionmentioning
confidence: 99%